2014
DOI: 10.4236/abb.2014.511101
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity Activity of <i>Bauhinia purpurea</i> Extract: Effect on Hormones and Lipid Profile in High Calorie Diet Induced Obese Rats

Abstract: Obesity is well recognized as a global public health concern and the quest continues to explore natural product-based novel therapeutics. Bauhinia purpurea finds its place in traditional medicine as an effective anti-ulcer, antiplatelet, wound healing and hypolipidemic agent. The present study investigated the effects of ethanolic extract of Bauhinia purpurea (EEB) on the changes in body weight, lean mass, fat free mass, fat percent, tissue and plasma lipid profiles, plasma glucose, insulin and insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…It has been observed that the disorders induced by high fat feeding resemble the human metabolic syndrome closely, with implications for the cardiovascular health [ 28 ]. We observed significant increase in liver weight in the HFHC group similar to the findings of Padmaja et al [ 29 ] who demonstrated that HFHC in experimental diets will cause lipid accumulation in some organs, especially the liver. C. nutans attenuated the HFHC induced changes without apparent toxicity to other organs, as seen from the organ weights index in Table 3 .…”
Section: Discussionsupporting
confidence: 90%
“…It has been observed that the disorders induced by high fat feeding resemble the human metabolic syndrome closely, with implications for the cardiovascular health [ 28 ]. We observed significant increase in liver weight in the HFHC group similar to the findings of Padmaja et al [ 29 ] who demonstrated that HFHC in experimental diets will cause lipid accumulation in some organs, especially the liver. C. nutans attenuated the HFHC induced changes without apparent toxicity to other organs, as seen from the organ weights index in Table 3 .…”
Section: Discussionsupporting
confidence: 90%
“…Serum leptin concentration in triton-induced hyperlipidemic rats increased versus CON rats. Leptin is formed by adipose tissue as fat packing reserves in the body, and it adjusts food consumption and energy disbursement [ 49 ], thus, indicating that the elevated serum leptin levels detected are likely a consequence of the increased fat accumulation. The leptin level reduced in hyperlipidemic rats that received PHEE in contrast to hyperlipidemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is authenticated by taxonomist in the department of Botany, Sri Venkateswara University, Tirupati, voucher number is 136 and specimen was preserved in departmental herbarium. The bark of B. purpurea was powdered, extracted with ethanol and further fractionated by column chromatography using different solvents [12]. The collected fractions were subjected to LC-MS analysis on 6520 Accurate Q-TOF (Agilent Santa Clara, CA) mass spectrometer to identify the major compounds.…”
Section: Isolation and Puri Cation Of Bauhiniastatin-1 (Bstn1)mentioning
confidence: 99%
“…of BSTN1 was suspended in 0.5% carboxymethylcellulose (CMC) and orally administered for 6 weeks from 13th week onwards using an intra-gastric tube. We selected these concentrations based on our initial pilot studies using solvent extracts [12]. IAEC approval (No:55/2012/(i)/a/CPCSEA/IAEC/SVU/MBJ, dated: 8-7-2012) were followed to conduct the animal experiments.…”
Section: Lipolysis Studiesmentioning
confidence: 99%
See 1 more Smart Citation